Portrait of Formal Islamic Education in the Wetu Telu Bayan Lombok Indigenous Community - Sumiadi, Raden (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to describe the picture of Islamic education in the Wetu Telu Bayan indigenous community who still firmly hold local traditional values. This research is qualitative research using a fhenomenology approach. In research, researchers act as the main instrument, data are obtained through interviews, observations and documentation activities and analyzed using the Miles & Huberman model, while the validity of the data is confirmed through extending the observation period, increasing persistence, triangulation, and focus group discussion. The results showed that the process of Islamic education in the indigenous people of wetu telu Bayan was carried out through formal educational institutions pursued through Madrasah Ibtidaiyah, Madrasah Tsanawiyah and Madrasah Aliyah.